No causal association between plasma cystatin C and cardiovascular diseases: Mendelian randomization analyses in UK biobank - Tu, Jingjing; Xu, Ying; Guo, Xu; Zhang, Jiayu; Xu, Duo; Han, Liyuan; Wang, Yue; Zhang, Boya; Sun, Hongpeng (Frontiers in Medicine, 2023)
Background We aimed to determine whether the plasma cystatin C is a causal risk factor for cardiovascular events, stroke, myocardial infarction (MI), and cardiovascular disease (CVD) mortality by conducting Mendelian randomization (MR) designs. Methods Our study included 277,057 individuals free of CVDs or cancer at baseline in the UK Biobank. The genetic scores of plasma cystatin C comprising 67 single-nucleotide polymorphisms were calculated on the basis of data from a large genome-wide association study. By stratifying the genetic score, we conducted cox regression to assess the relationship between plasma cystatin C and CVDs. In this study, linear MR analysis was used to estimate the causal association between plasma cystatin C and CVDs. Results Observational analyses showed that plasma cystatin C concentrations were associated with the risk of CVDs [hazard ratios (HR) per standard deviation (SD) 1.09, 95% confidence interval (CI); 1.07–1.10] and CVD mortality (1.14, 1.11–1.17). Among CVDs, plasma cystatin C were associated with stroke (1.10, 1.08–1.11) and MI (1.08, 1.07–1.10). Linear MR analysis did not provide evidence of a causal association between plasma cystatin C and the risk of CVDs [odds ratio (OR) per SD 0.96, 95% CI;0.90–1.03], stroke (0.96, 0.93–1.01), MI (0.97, 0.91–1.03), and CVD mortality (0.98, 0.96–1.01), with consistent estimates from sensitivity analyses. Conclusion Observational findings indicated that higher plasma cystatin C is associated with a higher risk of CVDs; According to MR studies, there is no causal association between plasma cystatin C and the risk of CVDs and CVD mortality.